Physical environment modulates the behavioral responses induced by chemical stimulation of dorsal periaqueductal gray in mice - Carvalho-Netto, E. F.; Markham, C.; Blanchard, D. C.; Nunes-de-Souza, R. L.; Blanchard, R. J. (Elsevier B.V., 2006)
In order to investigate the relationship between behaviors elicited by chemical stimulation of the dorsal periaqueductal gray (dorsal PAG) and spontaneous defensive behaviors to a predator, the excitatory amino acid D,L-homocysteic acid (5 nmol in 0.1 mu l), was infused into the dorsal PAG and behavioral responses of mice were evaluated in two different situations, a rectangular novel chamber or the Mouse Defense Test Battery (MDTB) apparatus. During a 1-min period following drug infusion, more jumps were made in the chamber than in the MDTB runway but running time and distance traveled were significantly higher in the runway. Animals were subsequently tested using the standard MDTB procedure (anti-predator avoidance, chase and defensive threat/attack). No drug effects on these measures were significant. In a further test in the MDTB apparatus, the pathway of the mouse during peak locomotion response was blocked 3 times by the predator stimulus (anesthetized rat) to determine if the mouse would avoid contact. Ninety percent of D,L-homocysteic treated animals made direct contact with the stimulus (rat), indicating that D,L-homocysteic-induced running is not guided by relevant (here, threat) stimuli. These results indicate that running as opposed to jumping is the primary response in mice injected with D,L-homocysteic into the dorsal PAG when the environment enables flight. However, the lack of responsivity to the predator during peak locomotion suggests that D,L-homocysteic-stimulation into the dorsal PAG does not induce normal antipredator flight. (c) 2006 Published by Elsevier B.V.
Keywords: D,L-homocysteic acid; dorsal periaqueductal gray; aversion; mouse defense test battery; defense reactions; mice